1996
DOI: 10.1108/09615539610113064
|View full text |Cite
|
Sign up to set email alerts
|

Computer simulation of liquid encapsulated vertical bridgman crystal growth: pseudo steady‐state calculations

Abstract: A pseudo steady‐state model is developed to study heat transfer, fluid flow, and the interface shape in the liquid encapsulated vertical Bridgman crystal growth. The model, which is governed by momentum, heat, and overall mass balances in the system, is solved by a finite‐volume/Newton method. Flow and temperature fields, as well as unknown melt/crystal and melt/encapsulant interfaces, are calculated simultaneously. Sample calculations are mainly conducted for the GaAs/B2O3/PBN system. Calculated results for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1997
1997
2000
2000

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…To reduce the concavity of the growth interface further, a typical way for Bridgman growth is to lower the cold zone temperature or to increase the thermal gradient near the interface [10,16]. The results are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To reduce the concavity of the growth interface further, a typical way for Bridgman growth is to lower the cold zone temperature or to increase the thermal gradient near the interface [10,16]. The results are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For puri®cation, mixing is also important on its eciency. In general, tuning the furnace con®gurations to control the melt ¯ow and thus the interface shape and mixing is typical, but it is usually dicult and less ¯exible [2,3]. Therefore, using external forces to control crystal growth has been widely adopted [ 4± 15].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, numerical simulation is attractive for the establishment of the optimum furnace design and growth conditions, and many numerical studies have been reported [6]. A pseudo steadystate has been assumed in numerous studies [7][8][9][10][11][12][13][14][15][16]. Recently, three-dimensional calculations on the VB crystal growth system have been reported [17,18].Kim and Brown have performed a transient analysis on the VGF [19] and VB [20,21] crystal growth systems by the finite element method.…”
mentioning
confidence: 99%